Insights into promoter-enhanced aqueous phase CO hydrogenation over Co@TiO2 mesoporous nanocomposites. (15th February 2022) - Gahtori, Jyoti; Singh, Gurmeet; Tucker, Chelsea L.; van Steen, Eric; Biradar, Ankush V.; Bordoloi, Ankur
Graphical abstract: Highlights: Efficient and facile approach to prepare promotors embedded support with high surface area. Enhanced CO conversion by utilizing low temperature and aqueous reaction media. The remarkable catalytic activity of 1.75 molCO molCo −1 h −1 corresponding to 70% CO conversion. MnO enriched the Co dispersion and enhanced the CO adsorption, which further improved the CO dissociation. CO conversion rates were modelled well by standard Fischer-Tropsch empirical rate expressions. Abstract: The particle sizes and metal support interactions play a pivotal role in Fischer Tropsch synthesis. Herein, promoter-embedded Co/TiO2 mesoporous nanocomposites with a high surface area were synthesized through a templated assisted solvothermal method comprising highly dispersed spherical shaped Co nanoparticles on titania nanoparticles of less than 10 nm. Moreover, Fischer Tropsch synthesis in aqueous media, rather than wax-slurry, is a new and relatively attractive approach to improve product selectivity and catalyst isolation. The Aqueous phase Fischer-Tropsch (AFTS) is a unified catalytic process to improve CO conversion and enhance selectivity towards higher hydrocarbon (C5+ ) at low temperatures. The performance under aqueous phase CO hydrogenation was investigated with varying cobalt, platinum, and manganese promoter concentrations to obtain an optimized catalyst recipe for AFTS. The metal support interaction has been studied with the help of temperature-programmed reduction (TPR) couple with XPS and HRTEM analysis. Moreover, the dispersibility of the active species was demonstrated through H2 chemisorption coupled with pulse reoxidation experiments. The CO-TPD and STEM analysis have been performed to understand the role of manganese during the reaction. The reaction parameters have been optimized thoroughly by varying temperature and pressure conditions. The catalyst with the optimized recipe (3 M0.5P25C) and parameters performed the exceptional CO conversion at a rate of 1.75 molCO .molCo −1 .h −1 (excluding CO2 ) with 73% selectivity towards C5+ hydrocarbons with less than 5% methane. Additionally, despite the aqueous phase, CO conversion rates for 3M1P25C were kinetically modeled well by standard Fischer-Tropsch empirical rate expressions, with little H2 O term dependence.